Factors Affecting Road Traffic Accidents in the Kathmandu valley - Manandhar, Raju Bhai (International Research Journal of MMC, 2022)
Road traffic accidentis defined as an accident which takes place on the road between two or more objects, in which one is any kind of moving vehicle and the other a human being. The major objective of the study is to determine the factors affecting the road accident in Nepal. Respondents were targeted drivers of two-wheeled and four-wheeled vehicles. 98 respondents were selected through convenience sample technique. Quantitative data as nature and primary data as sources of information were considered for the study. Primary data were collected and analyzed in systematic way to derive the findings. A well-structured survey questionnaire was administered to collect the data. In this study, data were analyzed using mean, median, mode, standard deviation, variance and trend analysis. Based on the Likert scale question, poor road condition was considered as the first important cause, drunk driving was considered as the second important cause, and over speed was considered as the third important cause influencing the road accident in the Kathmandu valley.